Dynamic modulation of nonreciprocal absorption in a graphene-InAs hybrid structure under low magnetic field and small incident angles - Ming Qing, Ye; Liu, Jiao; Yang, Zhaoyan; Wei Wu, Liang; Gou, Yue; Wu, Jun; Li, Bingxiang (Optics letters, 2025)
Overcoming Kirchhoff's laws to achieve strong nonreciprocity enhances energy harvesting and thermal management. Current magneto-optical (MO) strategies need high magnetic excitation and large incident angles, hindering practicality. We designed a graphene-InAs hybrid for significant nonreciprocity between absorptivity and emissivity at small angles with just 0.16 T, showing practical potential. By tuning graphene's Fermi energy, nonreciprocity strength can be adjusted via resonance mode competition. This design offers new insights for dynamic nonreciprocal radiation devices under near-normal light and modest magnetic excitation, facilitating practical use.